PENERAPAN GAYA KEPEMIMPINAN TRANSAKSIONAL PADA KOPERASI SIMPAN PINJAM PENGEMBANGAN PEDESAAN (KSP3) NIAS - Yurmanius Waruwu; Juang Solala Laiya (Jurnal Ekonomi dan Bisnis Nias Selatan, 2026)
This study aims to identify and describe the implementation of transactional leadership style at the Rural Development Savings and Loan Cooperative (KSP3) Nias. Transactional leadership is an approach that emphasizes exchanges between leaders and subordinates through a system of rewards and supervision to achieve organizational targets. This research employs a descriptive quantitative method with a single variable. The population consists of all leaders at KSP3 Nias, totaling 36 individuals. The sampling technique used is saturated sampling (census), in which the entire population serves as respondents. Data were collected through questionnaires that had been tested for validity and reliability, supported by observation and documentation. The data analysis technique used is descriptive statistical analysis by calculating the mean score and frequency distribution. The results show that the implementation of transactional leadership at KSP3 Nias falls into the High category, with an average score of 3.55. Specifically, the Contingent Reward indicator is the most dominant dimension, with a score of 4.25 (Very High), followed by Active Management by Exception with a score of 4.10 (High). Meanwhile, the Passive Management by Exception indicator falls into the Low category (2.30), indicating that leaders are responsive and not passive in addressing operational challenges. The conclusion of this study is that the leaders of KSP3 Nias have implemented firm and measurable leadership principles in maintaining cooperative stability. However, it is recommended that they begin integrating a transformational leadership approach to enhance employees’ long-term loyalty beyond material aspects.